Formação Continuada de Educação em Relações Étnico-Raciais para professores(as) da Educação de Jovens e Adultos - EJA da cidade de João Monlevade - MG - Marinete da Silva Morais (2019)
The research aims to understand how the theme of Ethnic-Racial Relations Education is worked on the pedagogical practice of teachers of the Youth and Adult Education (EJA) modality in the municipal network in João Monlevade. The relevance of carrying out the present proposal finds in this sense social support since it seeks to problematize a thematic that is significant for Brazilian society, namely: investigate Continued Teacher Training, EJA and Ethnic-Racial Relations Education (ERER). The research is based on the perspective of a qualitative approach, was carried out in a school of the municipal network located in this municipality. To do so, we used as an instrument of data collection: documentary analysis, semi-structured interviews with 04 teachers (as), 01 pedagogue, 01 manager; and a wheel of conversation. The results obtained revealed the lack of knowledge on the part of the education professionals of ERER's pedagogical proposals. In addition, many of these professionals identified gaps in their initial and continuing education on the subject of ethnic-racial relations and EJA. The findings also pointed to the need for continued training to be carried out in service with a longer duration, as well as to approach in a qualified manner ERER as educational policy of João Monlevade. Since this is a research within the scope of the Professional Master's Degree, we conceive as the Educational Product the elaboration of the Continuing Education Training Course in Ethnic-Racial Relations for Teachers of Young and Adult Education - EJA in the city of João Monlevade - MG.